Pengolahan Limbah Kulit Buah dari Pedagang Jus Menjadi Eco Enzyme dalam Upaya Mengurangi Pencemaran Lingkungan - Meilinda Suriani Harefa; Ferdy Almsyah; Frans Frans; Roma Ulina Sitohang; Leli Sartika (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to analyze the process of processing fruit peel waste from juice traders into eco-enzymes as an effort to reduce environmental pollution. The research uses qualitative descriptive methods through direct observation, documentation, and literature studies. Fruit peel waste is fermented at a ratio of 1:3:10 (molasses : fruit waste : water) for three months under anaerobic conditions. The fermentation results show good eco-enzyme characteristics, characterized by a pH of 3, a fresh sour aroma, and a brownish color as an indicator of fermentation success. These findings show that the process of processing eco-enzymes from fruit peel waste can be done simply, cheaply, and environmentally friendly. In addition, the use of eco-enzymes has the potential to reduce the volume of organic waste disposed of in landfills and reduce water and soil pollution. The resulting eco-enzyme also has potential applications as natural cleaners, liquid fertilizers, and odor controllers. Thus, the treatment of fruit peel waste not only supports sustainable environmental management practices, but also encourages the implementation of the circular economy as well as community empowerment ecologically and economically.